Validity of the Parental Burnout Inventory Among Dutch Employees - Van Bakel, Hedwig J. A.; Van Engen, Marloes L.; Peters, Pascale (Frontiers in Psychology, 2018)
The purpose of this study was to validate the Parental Burnout Inventory (PBI) in a Dutch sample of working parents. The Dutch version of the PBI and questionnaires about work were administered to 627 working parents, with at least one child living at home. We investigated whether the tri-dimensional structure of the PBI held in a sample of male and female employed parents. Furthermore, we examined the relationships between PBI and the constructs work-related burnout, depressive mood, parenting stress and work-family conflict, which we assessed with widely used and validated instruments, i.e., emotional exhaustion [a subscale of the Dutch version of Maslach’s Burnout Inventory], a Dutch Parental Stress Questionnaire and Work-Family Conflict. The results support the validity of a tri-dimensional parental burnout syndrome, including exhaustion, distancing and inefficacy. Low to moderate correlations between parents’ burnout symptoms and professional exhaustion, parenting stress, depressive complaints and work-family conflict experiences were found, suggesting that the concept of PBI differs significantly from the concepts of job burnout, depression and stress, respectively. The prevalence of parental burnout confirms that some parents are extremely exhausted by their parental role. However, the number of Dutch employees reporting extreme parental burnout is rather low.